1976
DOI: 10.1111/j.1550-7408.1976.tb03795.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of an Unidentified Protozoon in the Epithelium of Rainbow Trout Exposed to Water with Myxosoma cerebralis*

Abstract: An intracellular protozoon was discovered in the epithelium of young rainbow trout (Salmo gairdneri) exposed for as short a time as 1 hr to water known to contain infective stages of Myxosoma cerebralis. Light- and electron-microscopic examination of this tissue revealed what appeared to be a proliferative stage (presumptive schizont) of a sporozoon; other possible stages in the life cycle were also observed. The relationship of this unidentified protozoon of M. cerebralis remains unresolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 2 publications
1
11
1
Order By: Relevance
“…The findings also relate to work described by Daniels et al (1976), who found similar forms in epihelia of fish exposed to undefined infective agents for whirling disease, but did not establish a relation to actual disease. In both that study and the present study fish were exposed to whirling disease infectivity.…”
Section: Discussionsupporting
confidence: 50%
“…The findings also relate to work described by Daniels et al (1976), who found similar forms in epihelia of fish exposed to undefined infective agents for whirling disease, but did not establish a relation to actual disease. In both that study and the present study fish were exposed to whirling disease infectivity.…”
Section: Discussionsupporting
confidence: 50%
“…These cells then undergo an endogenous cleavage producing an inner secondary cell within an enveloping primary cell. Secondary cells then proliferate through rapid, synchronous mitosis, and the host cell nucleus is compressed between the large parasitic aggregate and the host cell plasmalemma (Daniels et al 1976; El‐Matbouli et al 1995). The secondary cells then undergo endogenous divisions to produce new cell‐doublets with an enveloping cell and inner cell.…”
Section: Life Cycles and Developmentmentioning
confidence: 99%
“…However, the articles on the portals of entry of myxosporeans to fish are limited only to research on Myxobolus cerebralis (Daniels et al 1976, Markiw 1989. It has been suggested that M. cerebralis penetrated through the skin and/or gills of fish as evidenced by the presence of development stages in the skin, fins, buccal cavity and digestive tract of fish exposed to the infective stage.…”
Section: Introductionmentioning
confidence: 99%